1998
DOI: 10.1046/j.1464-410x.1998.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and histological studies of the contralateral testes in two different intra‐ and extra‐abdominal rat models of unilateral cryptorchidism

Abstract: Objective  To investigate the effect of location of the testis on both testicular development and fertility in unilateral cryptorchidism. Material and methods  Forty‐nine Wistar King A newborn male rats were divided into three groups. In group 1 (15 rats) intra‐abdominal unilateral cryptorchidism were created by the intra‐abdominal fixation of the testis in the neonatal period. In group 2 (16 rats) extra‐abdominal unilateral cryptorchidism was created by extra‐abdominal fixation of the gubernaculum in the neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
3
10
0
2
Order By: Relevance
“…It has been reported that the ST diameters of unilateral undescended testes in adult rats decrease when compared with those of the descended testes and control group. 35 , 36 In our study, it was also observed that the ST diameters of the undescended testes decreased in the prepubertal, pubertal, and adult periods. The mean ST diameters of the undescended testes in rats given MC blocker were greater than in those rats not given MC blocker.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that the ST diameters of unilateral undescended testes in adult rats decrease when compared with those of the descended testes and control group. 35 , 36 In our study, it was also observed that the ST diameters of the undescended testes decreased in the prepubertal, pubertal, and adult periods. The mean ST diameters of the undescended testes in rats given MC blocker were greater than in those rats not given MC blocker.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, amounts of all histopathological parameters (except spermatogonia cells nuclei diameters in the scrotal testes) have showed moderate decrease in their values. Although the effect of unilateral cryptorchidism on ipsilateral testicular function may be attributable to the increase in ipsilateral testicular temperature, there is much controversy concerning the mechanisms that mediate the detrimental effect of unilateral cryptorchidism on contralateral testicular function (Salman et al ., ; Zakaria et al ., ; Watts et al ., ; Zivkovic et al ., ). It has demonstrated an increase in contralateral testicular blood flow and temperature in animals with unilateral cryptorchidism (Ono & Sofikitis, ; Kaki & Sofikitis, ; Saalu et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of unilateral cryptorchidism on the contralateral testes have been described by many authors in relation to subfertility (Salman et al ., ; Ono & Sofikitis, ; Zakaria et al ., ; Kaki & Sofikitis, ; Watts et al ., ; Zivkovic et al ., ; Saalu et al ., ,b). In our study, amounts of all histopathological parameters (except spermatogonia cells nuclei diameters in the scrotal testes) have showed moderate decrease in their values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les résultats d'une étude expérimentale réalisée sur deux groupes de rats : un premier groupe ayant une cryptorchidie unilatérale intraabdominale et un second groupe ayant une cryptorchidie unilatérale extra-abdominale ont montré que les structures histologiques dans le premier groupe de testicule induit cryptorchide sont plus altérées alors que l'histologie testiculaire est proche de la normale lorsque le testicule est bas situé. Les auteurs de cette étude concluent que la fertilité serait plus altérée lorsque le testicule siège en intraabdominal [19]. Cela peut être dû à l'augmentation de la température qui inhiberait le développement histologique du testicule et serait donc un facteur supplémentaire d'aggravation des lésions cellulaires [20][21][22].…”
Section: Introductionunclassified